2014
DOI: 10.1038/srep03603
|View full text |Cite
|
Sign up to set email alerts
|

Visible and Infra-red Light Emission in Boron-Doped Wurtzite Silicon Nanowires

Abstract: Silicon, the mainstay semiconductor in microelectronic circuitry, is considered unsuitable for optoelectronic applications owing to its indirect electronic band gap, which limits its efficiency as a light emitter. Here we show the light emission properties of boron-doped wurtzite silicon nanowires measured by cathodoluminescence spectroscopy at room temperature. A visible emission, peaked above 1.5 eV, and a near infra-red emission at 0.8 eV correlate respectively to the direct transition at the Γ point and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…The absorption spectra as shown in Figure A‐E moves toward the visible range of the spectrum, as the sheet size increases. It can also be seen that the absorption spectra of B‐ and Zr‐doped structures (see Figure A,E) are in the visible range, which is also observed in Si nanostructures, and can be attributed to that these elements being active in the visible spectrum . For the P‐, C‐, and Si‐doped structures (see Figure B‐D), absorption spectra are in the UV to short‐wavelength visible spectrum, which is consistent with experiments .…”
Section: Resultssupporting
confidence: 81%
“…The absorption spectra as shown in Figure A‐E moves toward the visible range of the spectrum, as the sheet size increases. It can also be seen that the absorption spectra of B‐ and Zr‐doped structures (see Figure A,E) are in the visible range, which is also observed in Si nanostructures, and can be attributed to that these elements being active in the visible spectrum . For the P‐, C‐, and Si‐doped structures (see Figure B‐D), absorption spectra are in the UV to short‐wavelength visible spectrum, which is consistent with experiments .…”
Section: Resultssupporting
confidence: 81%
“…Experimental results have demonstrated increased absorption in nanowire-patterned silicon as compared with planar silicon across the visible and near-infrared regions of the electromagnetic spectrum [22]. Although Si-IV nanowires with direct-gap transitions have been synthesized through chemical vapor deposition methods [13], we show here that Si-IV can be recovered in silicon nanowires previously prepared through chemical etching after near-hydrostatic compression up to 17 GPa in a diamond anvil cell (DAC). These results demonstrate the feasability of designing PCs with cubic silicon and recovering exotic phases after pressurization while maintaining complex morphologies created through lithographic processing.…”
mentioning
confidence: 91%
“…Si-III (body-centered cubic) and Si-IV (diamond hexagonal), however, are stable at atmospheric pressure and have been synthetisized [4,12,13] as well as recovered from high-pressure phase transitions [14,15]. While Si-III is a semimetal [14] and could have applications in electronics, Si-IV is a semiconductor with a reported indirect band gap near 0.8-0.9 eV and direct transition at 1.5 eV [13]. The direct transition for Si-IV makes * peterpz@uw.edu FIG.…”
mentioning
confidence: 99%
“…20,21 This experimental scenario suggests that exploiting polytypism in group IV NWs could be an efficient way to enhance NWs optoelectronic performances while retaining the compatibility with existent Si technology. As regards as Si NWs, recent experimental and theoretical investigations seem to confirm this prediction: cathodoluminescence measurements on hexagonal-diamond Si NWs 22 show that these structures can emit visible light with a higher efficiency than cubicdiamond NWs; on the other hand, results of ab initio calculations 23 have demonstrated that strained hexagonal-diamond bulk Si could be employed as an active layer in photovoltaic devices with absorption properties that are more favorable than those of cubic-diamond Si.…”
mentioning
confidence: 92%